Pengembangan Media Permainan Ular Tangga untuk Kesadaran Guna Perilaku Kedisiplinan Siswa di SMA Negeri 4 Kota Serang - Hanny Putri Nirmala; Raudah Zaimah Dalimunthe; Meilla Dwi Nurmala (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
The study aims to develop a snake and ladder game media, in order to determine the awareness of students' disciplinary behavior at SMA Negeri 4 Kota Serang after using the snake and ladder game learning media. The method used is Research and Development (R&D) with the development of the 4D model. The results of the product feasibility test obtained an average value of 86%, which means it is very feasible to be implemented. Limited trials were conducted on The trial was conducted on 11 students of class X MIPA 6 SMAN 4 Kota Serang who were identified as having a low level of discipline. The results of the data analysis showed that although the majority of students showed good disciplinary behavior, there was a group of students with a low level of discipline. This indicates the need for innovative and fun learning strategies to increase awareness and disciplinary behavior, especially for students with low scores